Girls Growing Up in Late Victorian and Edwardian England. - Dyhouse, Carol (Routledge library editions. Women's history., 2012)
Girls learn about ""femininity"" from childhood onwards, first through their relationships in the family, and later from their teachers and peers. Using sources which vary from diaries to Inspector's reports, this book studies the socialization of middle- and working-class girls in late Victorian and early-Edwardian England. It traces the ways in which schooling at all social levels at this time tended to reinforce lessons in the sexual division of labour and patterns of authority between men and women, which girls had already learned at home. Considering the social anxieties that helped to.